Investigations for the Surface of the Oxide Semiconductor Changes by Reduction*Supported by the Far East University Research Foundation under Grant No FEU2013S03, and the Hansung University. (May 2016) - Kang, Bonghoon; Hwang, Sung-Tae
Abstract : Oxide semiconductor SrTiO3 single crystals are exposed to a reducing atmosphere H2 /N2 to induce the reduction of Ti 4+ to Ti 3+ and the release of oxygen from the lattice compensating the reduction of the Ti ions. In a reducing atmosphere H2 /N2 the optical edge brings about a red shift. The infrared reflection spectra suggest that the (11) STO single crystal surface can be terminated by the domain of the SrO or TiO2 alternative layer during the reduction. The anisotropy and asymmetry of optical second-harmonic intensity explain a slight shrinkage. The dielectric constant reaches about 6000 and shows almost frequency dependence at all temperatures. With the increasing temperature, the dielectric constant increases rapidly. The high temperature region and low temperature region have activation energies of 0.89 and 1.04, respectively.